Numerical solution for the model of RLC circuit via the fractional derivative without singular kernel - Atangana, Abdon; Nieto, Juan Jose (Advances in mechanical engineering, 2015)
The numerical approximation of the Caputo–Fabrizio fractional derivative with fractional order between 1 and 2 is proposed in this work. Using the transition from ordinary derivative to fractional derivative, we modified the RLC circuit model. The Crank–Nicolson numerical scheme was used to solve the modified model. We present the stability analysis of the numerical scheme for solving the modified equation and some numerical simulations for different values of the order of derivation.